Analysis of Abuse of Dominant Position through Secret Agreements by PT. Forisa Nusapersada - Winanda, Lutgardis Dianika; Irwan, Raden; Basuki, Rahmad; Warsono, Warsono; Pangaribuan, Zekson (CV. Publikasi Indonesia, 2025)
The regulation in Law Number 5 Year 1999 on the Prohibition of Monopolistic Practices and Unfair Business Competition broadly addresses prohibited agreements, activities, and dominant positions. This study uses a normative juridical research method with the aim of analyzing the closed agreements made by PT Forisa Nusapersada based on Law No. 5 of 1999, Commission Regulation No. 3 of 2009, and Commission Regulation No. 6 of 2010. The research specifically focuses on the abuse of the dominant position through the